PENDIDIKAN ISLAM PERSPEKTIF ZAKIAH DARADJAT - Nurlela, Siti; Azizah , Siti Nur; Rahayu, Siti; Sholihat, Siti; Rehani, Siti; Solihat, Siti (STAI Darul Qalam Tangerang, 2025)
Islamic education is an effort of physical and spiritual guidance at the level of individual and social life to develop human nature based on Islamic laws towards the formation of an ideal human being (insan kamil) who has a Muslim personality and commendable morals and is obedient to Islam so that he can achieve happiness in the world and the hereafter. The family is the first place where the education process takes place. Then continued with school and society. The difficulties in carrying out the task of educating are very pronounced, especially when faced with the reality that the influence of the environment is so strong, even surpassing the strength of other educational factors. At times like that, parents as the first educational force in the family environment must realize their role as educators completely towards their children. Departing from that background, the author then wants to discuss it in a thesis entitled